COVID-19 Vaccines in Inherited Retinal Degenerations (IRD), Fears, Ideas and Real Interactions - Vingolo EM (Clinical Ophthalmology, 2022)
Enzo Maria Vingolo Department of Surgery “Unit of Ophthalmology”, University “Sapienza” Polo Pontino, “A.Fiorini” Hospital, Terracina, 4120, ItalyCorrespondence: Enzo Maria Vingolo, Department of Surgery Unit of Ophthalmology, University Sapienza Polo Pontino, “A.Fiorini” Hospital, Terracina, 04120, Italy, Tel +393486500312, Email enzomaria.vingolo@uniroma1.itPurpose: In the COVID-19 pandemic era, vaccines are one of the most efficient weapons, as well established by WHO, that humans have, in all their variants (mRNA, AAV or others). Unfortunately, in western nations skepticism within different groups has been generated by the fast approval processes, driven by the urgent need to confront the rapid increase of hospitalized patients and number of deaths by regulation authorities as FDA and EMA. Moreover, several scientific and non-scientific perplexity, also amplified by the media, created hard no-vax strategies, that lead many patients to refuse vaccine administration. Also in this selected population higher rate of COVID-19 infections and severe diseases are registered and consequently there was an increase of death number. Furthermore, to avoid vaccine shots, people frequently ask exemption querying ophthalmological and systemic diseases, in this situation most patients affected with orphan ophthalmological conditions as inherited retinal degenerations have profound fears and doubt. The goal of our study was to ascertain if these fears are based on real facts and if there are interactions or severe visual impairment after each shot of vaccinations.Methods: Five hundred randomically selected patients affected by IRD at each patient was asked anonymously, number of vaccine administrations and eventually reported side effects.Results: Of 500 selected patients 61 (12,2%) did not underwent to Covid-19 vaccination, reasons were various (fear, laziness, caregiver unavailability etc.). Remaining 439 patients (87,8%) had first shot of vaccine. Only 30% of patients complained side effects of vaccine, none of them was serious.Conclusion: The number of patients is wide enough to draw some considerations: In IRD vaccination is safe, in all doses ocular side effects were reported only in one third of subjects and this is not different from the percentage shown by normal people, COVID-19 effects may be more dangerous than vaccine.Keywords: COVID-19, Retinitis pigmentosa, vaccination, inherited retinal degenerations